(untitled) (Research, Society and Development, 2020)
This is a teaching proposal using Digital Technologies (video production), based on a didactic sequence that addresses the chemical composition and metabolism of drugs through the self-medication theme. Participants were 46 3rd graders from a state public school. The proposal was implemented in two steps. In the first, the students surveyed, through the application of a questionnaire, about the practice of self-medication between family and community. In the second stage, the repercussions of the practice of self - medication for health were problematized, studying the chemical structures of the most used drugs, as well as their metabolization. From this, the students were instructed to produce videos about the most used drugs, considering the problematized and studied aspects. The analysis of the questionnaires shows the consumption of medicines as common practice among the interviewees. The students presented fragmented knowledge about the subject, with little information about the rational use of drugs. The approach through video production was pointed out by students as challenging and important for effective learning. The study of drugs through a daily situation, such as self-medication, is of paramount importance for the formation of critical and reflective citizens, as it involves their reality and implications for their health. Regarding chemical knowledge and video production, we understand that the strategy served as an articulator of learning, enabling the interaction between formal knowledge and world knowledge.